2023
DOI: 10.3389/fpls.2023.1240196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drip irrigation on yield, soil fertility and soil enzyme activity of different potato varieties in Northwest China

Fan Zhang,
Mengru Chen,
Jintao Fu
et al.

Abstract: The effects of different irrigation and fertilization on potato yield, soil fertility and soil enzyme activity of different varieties under drip irrigation fertilization mode were studied, which could provide support for selecting the best varieties in Northwest China. Three factors and three levels orthogonal experimental design method, a total of nine treatments. The three irrigation levels were W1 (100% crop evapotranspiration (ETC)), W2 (80% ETC) and W3 (60% ETC). The three fertilization levels were F1 (N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…N accumulated on the surface of the soil under film treatment, and the film slowed down the rate of NO 3 − -N migration, thereby increasing the content of NO 3 − -N in the film treatment [34,35]. The same results showed that soil moisture was the most important factor affecting the changes to soil nutrients, and drip irrigation could alleviate the adverse effects of drought stress on crops and promote the absorption and utilization of NO 3 − -N by roots [36]. Overall, increased soil moisture content promoted the process of microbial denitrifying bacteria and increased the risk of NO 3 − -N migration and discharge while reducing soil NH 4 + -N content, increasing the risk of NH 4 + -N leaching.…”
Section: Impact Of Irrigation Systems On the Soil Physicochemical Pro...mentioning
confidence: 82%
“…N accumulated on the surface of the soil under film treatment, and the film slowed down the rate of NO 3 − -N migration, thereby increasing the content of NO 3 − -N in the film treatment [34,35]. The same results showed that soil moisture was the most important factor affecting the changes to soil nutrients, and drip irrigation could alleviate the adverse effects of drought stress on crops and promote the absorption and utilization of NO 3 − -N by roots [36]. Overall, increased soil moisture content promoted the process of microbial denitrifying bacteria and increased the risk of NO 3 − -N migration and discharge while reducing soil NH 4 + -N content, increasing the risk of NH 4 + -N leaching.…”
Section: Impact Of Irrigation Systems On the Soil Physicochemical Pro...mentioning
confidence: 82%